Pengaruh Abu Serbuk Kayu Kulim dan Serbuk Tempurung Kelapa terhadap Kuat Tekan Beton - Putra, Andika Rahmawanto; Agustapraja, Hamam Rofiqi (Jurnal Talenta Sipil, 2024)
This research combines kulim wood dust and coconut shell powder as a substitute for concrete materials. Ash from kulim sawdust has silicca properties. Meanwhile, coconut shell powder can be mixed in concrete. This study aims to determine the effect of using kulim sawdust ash as a partial substitution of cement and coconut shell powder waste as a partial substitution of fine aggregate on compressive strength and to determine the ideal proportion of the percentage variation of added ingredients. Concrete planning uses an experimental method that refers to SNI 03-2834-2000, SNI 03-1974-1990 and the Unisla Concrete Practicum Guidebook. With a total sample of 12 test objects with the quality plan K-225. The results of the normal concrete compressive strength test with an N code of 19.55 MPa. The results of testing the compressive strength of concrete with added materials with code A1 are 19.29 MPa. The results of testing the compressive strength of concrete with added materials with code B1 are 18.84 Mpa. The results of testing the compressive strength of concrete with added materials with code C1 are 18.46 MPa. Based on the results of the study it was concluded that the added ingredients of kulim wood powder ash and coconut shell powder did not significantly affect the compressive strength of concrete and the higher the added material value the lower the concrete compressive strength value and the lower the added material value, the higher the concrete compressive strength value.